Prosody Analysis to Recognize Speech Disorders among the Elderly - Agus, Cecep; Alifah, Nur (Journal of Psycho Linguistics, 2025)
This study explores prosodic analysis as a method to recognize speech impairment in the elderly. The background shows that physiological and neurological changes often affect intonation patterns, rhythm, intensity, and vocal quality, thus impacting communication fluency. The method used was qualitative with in vivo voice recording, interviews, and signal analysis using sound processing software. The results found a decrease in pitch frequency range, slowness of speech rhythm, and decreased voice intensity, indicating a decline in phonation function among the elderly. The implication is that the prosodic approach can be an early screening tool, enabling more appropriate clinical and speech therapy interventions to maintain the quality of life of the elderly.